PENGARUH PELATIHAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT. BANK BJB KANTOR CABANG SUCI BANDUNG - Roro Watie Rachmawati (Jurnal Manajemen dan Pemasaran Jasa, 2016)
ABSTRACT                In this study a problem that occurs is the implementation of training and motivation are ineffective for employees in PT. Bank BJB Office Bandung, so that they are less than optimal performance. This study aimed to test the Training and Work Motivation Effect on Employee Performance in PT. Bank BJB Office Bandung. The population in this study is that all employees at PT. Bank BJB which amounted to 51 employees. The sampling technique used is census sampling technique, the sample set as many as 51 employees. This study uses a quantitative approach, the data for this study were obtained through questionnaires (questionnaire) which has been filled by the respondents who have been determined. Data analysis method used is the method of multiple linear regression analysis.               The results of the analysis of Pearson correlation 0.794 or 79.4 % which shows that the correlation between training and work motivation and performance of employees are in a strong relationship level, means that training and motivation has a positive and significant relationship to the performance variables. While the coefficient of determination 0.631 or 63.1 %, meaning that training and motivation has contributed 63.1 % of the employee's performance, while the remaining 36.7 % is influenced by other variables which is not examined. Training and motivation are ineffective for employees in PT Bank BJB Office Bandung as a whole is not yet optimal.